Intention to migrate among engineering students in Malaysia / Fahim Wazir - Fahim , Wazir (2019)
Human capital and innovation play a crucial role for an economic growth of a country based on the Endogenous Growth Model. Many developing countries including Malaysia has adopted this model to pursue in becoming high-income nation. Thus, strategies such as the Higher Education Strategic Plan are implemented with the aim to increase the number of human capital with tertiary education up to 33% specifically in the field of science, engineering and ICT by 2020. However, Malaysia are struck by the flight of high skilled human capital to a foreign country with no intention to return home. In 2000, there were 184 thousand Malaysians with tertiary-education are migrated for economic reasons, in 2010, it was estimated that approximately 1 million Malaysian are living abroad. Brain drain could hindered Malaysia’s economic growth due to the outflow of skilled workers and may distort growth of innovation of the country. The objective of this study is to investigate the intention to migrate among engineering students, if any and to determine the factors that influence them to migrate abroad. Sample for this study are engineering students from selected public and private universities. This research utilized quantitative methodology, which 400 questionnaires has distributed to engineering undergraduates. Result shows that majority of engineering students have the intention to migrate to Japan, United Kingdom and Australia. Female students are more likely to migrate as compared to male students. Additionally, the study found that attractive salary, employment opportunity, and having family and friends living abroad are among the reasons to move abroad. Hence, a more comprehensive policies and initiatives are crucial in order to retain skilled labor in Malaysia.